Horticulture: potential to food and nutritional security - Singh, A. K.; Janakiram, T.; Das, Manish (Indian Farming, 2018)
Fruits and vegetables rich in nutritive value like aonla, ber and bael can be grown in degraded lands and concrete efforts are needed from different agencies to reclaim such marginal and degraded soils and bring them under productive cultivation. Focused efforts are required to promote containergrowing and kitchen gardening in the urban areas to meet the nutritional requirements of the families. The technology for container-growing of fruits and vegetables is available in a number of research organizations. Such technologies can be popularized among the urban population to ensure adequate nutritional supplementation. The demand for organic fruits and vegetables is increasing at a rapid pace. Such horticultural produce grown through organic means is nutritionally superior and free from the injurious pesticide residues that are otherwise found in inorganically grown produce. Growing awareness, therefore, about the organic fruits and vegetables would further enhance the supply of nutrients in a safer way. Henceforth the country has to gear itself up to prevent and combat the dual burden of under nutrition and over nutrition and associated health problems. Horticulture is the panacea.